The Influence Of Business Ethics Practices On Generation Z Customer Satisfaction On Shopee E-Commerce Application - Rachman, Muhamad; Sikki, Nurhaeni (Commercium : Journal of Business and Management, 2024)
This research is titled "The Influence of Business Ethics Practices on Generation Z Customer Satisfaction on Shopee E-Commerce Applications". This research aims to find out business ethics in Shopee E-Commerce, to find out customer satisfaction in Shopee E-Commerce and to find out how much business ethics influence customer satisfaction in Shopee E-Commerce. This study uses a quantitative method with a type of research. Sampling is using error sampling with a sample of 100 people. Data analysis techniques are descriptive and inferential tests and simple linear regression. The conclusion of this study is that the Influence of Business Ethics Practices on Generation Z Customer Satisfaction on the Shopee E-Commerce Application is included in the good category. So there needs to be other factors developed for further research.